SITUATION OF DRUGS FOR TREATMENT INTESTINAL INFECTION (Vietnam Journal of Community Medicine, 2021)
Objective: To survey the use of drugs to treat intestinal infection at Can Tho Children’s Hospital. Objects and methods: Cross-sectional retrospective descriptive study on 400 medical records of pediatric patients diagnosed with intestinal infection in Can Tho City Children’s Hospital in 2019. Result: There were 353 pediatric patients using rehydration and electrolytes measeurement, ORS with the highest frequency was 38.66%. The antibiotic with the highest frequency of use was the beta-lactam 3rd group. In which, Cefotaxim had the most use frequency. Single regimen of cefotaxim used the most with a frequency of 70.06%. Meanwhile, the antibiotic regimen cefotaxime combined with tobramycin was the highest in the combined regimen with 57.14%. Up to 70 cases changed the regimen due to ineffective results and 22 cases changed the regimen due to its effectiveness, reducing the amount of antibiotics. The first regimen with the highest frequency of change was the cefotaxim regimen with 33 cases. The 2nd regimens changed with the highest frequency were cefotaxim regimen and regimen of cefotaxim combined with tobramycin with 5 cases. The third change of regimen was mostly from combination antibiotic regimen to single regimen. Conclusion: Rehydration and electrolyte measures were mainly ORS. Antibiotics used mainly in the beta-lactam 3rd group, Cefotaxim had the highest frequency of use. Cefotaxim was used the most frequency in a single regimen. The antibiotic combined regimen between cefotaxime and tobramycin was the highest use in all combined regimens. Changing treatment regimen was mainly due to the ineffective effect.
Keywords: Situation of drug use, intestinal infection